Legal Protection for Wives in Murder Cases: An Islamic Law and Positive Law Perspective - Muhammad Yasir; Syamsiah Nur; Rina Septiani; Solihah Sari Rahayu; Ratna Rintaningrum; Karimuddin Abdullah Lawang (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the legal protection for wives in murder cases from the perspectives of Islamic law and positive law. In the context of Islamic law, the principle of justice governs the rights of wives, including protection against domestic violence. However, the implementation of this principle in judicial practice still faces various challenges. On the other hand, Indonesia's positive law, despite regulating women's protection through the Law on the Elimination of Domestic Violence (UU PKDRT), also encounters obstacles in effective law enforcement, particularly in cases of violence resulting in murder. This study also discusses the comparison of sanctions imposed on perpetrators of wife murder in both legal systems, highlighting significant differences in the determination and implementation of penalties. Additionally, this research identifies major challenges in law enforcement, such as the lack of gender sensitivity among law enforcers and the limited access victims have to effective protection. The proposed policy recommendations include strengthening regulations on wife protection, enhancing the capacity of law enforcement officers, and expanding access to legal and psychological services for victims. This study contributes to the development of a more responsive legal policy for women's protection.